2021
DOI: 10.21203/rs.3.rs-192099/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

miR-24 targets SARS-CoV-2 co-factor Neuropilin-1 in human brain microvascular endothelial cells: Insights for COVID-19 neurological manifestations

Abstract: Neuropilin-1 is a transmembrane glycoprotein that has been implicated in several processes including angiogenesis and immunity. Recent evidence has also shown that it is implied in the cellular internalization of the severe acute respiratory syndrome coronavirus (SARS-CoV-2), which causes the coronavirus disease 2019 (COVID-19). We hypothesized that specific microRNAs can target Neuropilin-1. By combining bioinformatic and functional approaches, we identified miR-24 as a regulator of Neuropilin-1 transcription… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 89 publications
1
15
0
Order By: Relevance
“…Due to the fact that NRP-1 is involved in endothelial-dependent immune responses in the human brain, Mone et al attempted to identify microRNAs (miRNAs) that specifically target NRP-1 in brain microvascular endothelial cells representing the blood-brain barrier. Using Targetscan 7.2, the authors identified hsa-miR-24-3p (miR-24), which is probably a modulator of neuropilin-1 mRNA expression [32]. Therefore, miR-24 has been indicated as a potentially therapeutic target focused on the reduction in endothelium-dependent inflammation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the fact that NRP-1 is involved in endothelial-dependent immune responses in the human brain, Mone et al attempted to identify microRNAs (miRNAs) that specifically target NRP-1 in brain microvascular endothelial cells representing the blood-brain barrier. Using Targetscan 7.2, the authors identified hsa-miR-24-3p (miR-24), which is probably a modulator of neuropilin-1 mRNA expression [32]. Therefore, miR-24 has been indicated as a potentially therapeutic target focused on the reduction in endothelium-dependent inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, miR-24 has been indicated as a potentially therapeutic target focused on the reduction in endothelium-dependent inflammation. Additionally, it has been found that miR-24 decreases the blood-brain barrier permeability in response to vascular endothelial growth factor (VEGF), which has been indicated as one of the most studied ligands of NRP-1 [32]. Moreover, it has been revealed that VEGF-A sensitizes nociceptor activity which initiates the sensation of pain in the central nervous system [33,34].…”
Section: Resultsmentioning
confidence: 99%
“…Though ECs were not included in the cell line experiments, the scRNA-seq data from human lung and olfactory epithelium emphasized the highest levels of NRP1 in ECs, implying that NRP1 may play a potential role in the reciprocal action between SARS-CoV-2 and endothelium [ 59 ]. In fact, NRP1 is a well-characterized co-receptor of vascular endothelial growth factor (VEGF) in ECs [ 62 , 63 ], its cell surface expression on ECs has been well acknowledged.…”
Section: Evidence Of Direct Infection Of Ecs By Sars-cov-2mentioning
confidence: 99%
“…NRP1 is a transmembrane receptor that binds to SARS-CoV-2 proteins, improving the entry of the virus into the CNS by facilitating the fusion of membranes in neuronal tissue. In addition, it induces viral replication, neuronal death, and vWF secretion in endothelial cells, accompanied by angiogenesis and platelet activation, which exacerbates CNS damage and increases the risk of CVD [142][143][144]. Usually, miR-24 is capable of repressing the expression of NRP1; however, a decrease in this miRNA has been shown in COVID-19, which could increase the expression of NRP1 and, along with this, increase the neurological damage caused by the virus entering neuronal cells [142].…”
Section: Neurological Damagementioning
confidence: 99%